Current Status and the Future of Protection and Utilization of Personal Information at Medical Facilities Based on the Understanding of Related Regulations - Uchikura, Takeshi; Momo, Kenji; Sasaki, Tadanori (YAKUGAKU ZASSHI, 2021)
In September 2015, “the Act on the Protection of Personal Information” was amended. Accordingly, “the Ethical Guidelines for Medical Research Involving Human Subjects” were also amended. “The Act on Anonymized Medical Data That Are Meant to Contribute to Research and Development in the Medical Field,” which came into effect in May 2018, aims to collect and utilize medical information of each patient from medical institutions for the purpose of research and development in the medical field. Thus, the rules of personal information that need to be followed are changing considerably in the balance between importance of protection and utilization for medical development. Therefore, health care professionals and researchers are required to fully understand the current situation and the future.